1991
DOI: 10.1002/yea.320070105
|View full text |Cite
|
Sign up to set email alerts
|

Yeast mutants with increased bacterial transposon Tn5 excision

Abstract: Five complementing recessive mutations that exhibit increased bacterial transposon Tn5 precise excision in yeast Saccharomyces cerevisiae were obtained by ethylmethanesulfonate treatment. One of these mutations (tex1) was submitted to extensive genetic analysis. tex1 is a recessive temperature-sensitive mutation resulting in a 20-100-fold increase in Tn5 excision. It also has increased frequencies of ochre mutation reversion, of forward mutation to canavanine resistance, and loss of chromosome III or its right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
5
18
1
Order By: Relevance
“…The LIRs could increase replication slippage type mutations several hundred-fold in yeast (29)(30)(31)47). Recently, Canceill and Ehrlich (13) demonstrated that while an LIR can inhibit in vitro replication by the E. coli Pol3 holoenzyme, slippage could occur between small direct repeats at the base of the LIRs depending on replication conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LIRs could increase replication slippage type mutations several hundred-fold in yeast (29)(30)(31)47). Recently, Canceill and Ehrlich (13) demonstrated that while an LIR can inhibit in vitro replication by the E. coli Pol3 holoenzyme, slippage could occur between small direct repeats at the base of the LIRs depending on replication conditions.…”
Section: Discussionmentioning
confidence: 99%
“…An insertion of an LIR into a gene can stimulate interchromosomal heteroallelic recombination as much as 10-fold (28). Previously, LIRs were shown to induce deletions between small surrounding direct repeats in bacteria and yeast (17,23,(29)(30)(31)47). In transgenic mice, LIRs are mitotically unstable and lead to insertions or deletions (16).…”
mentioning
confidence: 99%
“…The reduced expression of Pol1p has been shown to increase the efficiency of mating between two MAT␣ haploids (20). This "illegitimate" mating is usually a consequence of the deletion or mutation of the MAT␣ locus in one of the two mated haploids (10,20,23). To determine whether a reduced expression of Pol3p elevated illegitimate mating, we first used a streak mating assay (Fig.…”
Section: Vol 28 2008 Low Levels Of Pol3p Induce Fragile Site Instabmentioning
confidence: 99%
“…This mutant (initially named tex1) was isolated in a strain that exhibited an increased excision rate of a bacterial transposon with long terminal repeats inserted within a yeast gene (7). The pol3-t allele, which encodes a mutation (Gly 641 to Ala 641 ) (51) located near the putative nucleotide binding and active-site domains of the enzyme (58), is thought to diminish the rate of lagging-strand synthesis resulting in long stretches of singlestranded DNA on the lagging-strand template (8).…”
mentioning
confidence: 99%